Little Miss Tidy - Hargreaves, Roger (World international Limited, 1990)
Little Miss Tiny is the 5th book in the Little Miss series. Little Miss Tiny isn't just small, she's tiny. Little Miss Tiny is tinier than Mr. Small. Little Miss Tiny is picked on because she is so small.
Keywords: Juvenile Fiction-Book